Logic Algorithm for contour following task: An evaluation using Adept SCARA Robot - Anton, S P; Samsi , Md. Said; M.A., Burhanuddin (IJCSES, 2010)
This paper presents the performance evaluation of logic algorithms for contourfollowing task in order to automate the manual programming process. The main objective of this work is to evaluate and compare the performance of single logic and dual sensor logic algorithmsfor autonomous contourfollowing in industrial robot. Thosi atgorithms have been implemented using Adept SCAM robot. The algorithms were tested on a semicircle object o/ 40 millimeter radius. The result shows mean of error and standard deviation value of single logic algorithm is a bit lower than clual sensar logic algorithtn.